The Impact of a Study Abroad Experience on Preservice Teachers' Dispositions and Plans for Teaching English Language Learners. Issue 1 (2nd January 2017) - Pilonieta, Paola; Medina, Adriana L.; Hathaway, Jennifer I.
ABSTRACT: This study explored how a study abroad experience affected preservice teachers' (PSTs') dispositions towards and plans for teaching English Language Learners (ELLs). This qualitative study involved 16 elementary education initial licensure PSTs who participated in a 2-month study abroad trip to Germany. Data in the form of surveys, interviews, and reflections were collected. The PSTs' experiences left them feeling like outsiders, fostering greater empathy for ELLs. As the PSTs faced the challenges of studying abroad, they developed ways of coping, which influenced their dispositions toward ELLs and the accommodations they wanted to make when teaching ELLs in their future classrooms. A model of the PSTs' learning progression within the study abroad experience is offered as a lens to consider their transformations. Findings suggest it would be beneficial for educators traveling abroad with PSTs to find ways to make explicit the connections between personal encounters and future teaching experiences.